2019
DOI: 10.1111/inr.12571
|View full text |Cite
|
Sign up to set email alerts
|

Developing a strategic model of participation in policy development for nurses

Abstract: Aim To develop a strategic model of participation in policy development for nurses in Thailand. Background Public health policies inevitably affect nursing practice, service delivery and the nursing workforce. Available evidence indicates that nurses have minimal participation in policy development. Introduction Nurses’ participation in public health policy development is essential to developing and maintaining an efficient, high‐quality healthcare system. Methods The Delphi method was used to develop the stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…Leavitt (2009) suggested that strong support from the management team is necessary for facilitating nurses’ involvement in policy development. According to Wichaikhum et al (2020), nurse leaders should be knowledgeable about professional issues and health policy processes either through formal curricular courses or through in‐service educational meetings.…”
Section: Discussionmentioning
confidence: 99%
“…Leavitt (2009) suggested that strong support from the management team is necessary for facilitating nurses’ involvement in policy development. According to Wichaikhum et al (2020), nurse leaders should be knowledgeable about professional issues and health policy processes either through formal curricular courses or through in‐service educational meetings.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by including APNs at the health policy table where decisions are made for local, regional or national PC programs. Yet, there is evidence that nurses have limited participation and could benefit from a strategic model that develops awareness and capacity for policy involvement, strengthening decision‐making within the team (Wichaikhum et al 2020). For US nurses, r evaluing promotion, prevention and public health would need to be strongly embraced.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses’ participation in policy making extends the caring spirit of the nursing profession and promotes public health [ 2 ]. Nurses are valuable sources of insight and information affecting the formulation of health policies, and can prevent unintended consequences [ 94 ].…”
Section: Directives To Improve Nurses’ Job Conditions and Securitymentioning
confidence: 99%